OPTIMALISASI PERAN KADER DALAM PEMBENTUKAN KELOMPOK PENDUKUNG ASI UNTUK MEWUJUDKAN KADARSIE (KELUARGA SADAR ASI EKSKLUSIF) - Kurniyati Kurniyati; Yusniarita Yusniarita; Wenny Indah Purnama Eka Sari; Yenni Puspita (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
The success of Exclusive Breastfeeding requires many people to participate. One of those who need to participate is posyandu cadres. Cadre is a partner of the public health center to help carry out the programs and activities of the public health center to achieve equitable health coverage for infants and toddlers. One of those who need to participate is posyandu cadres. The purpose of this Community Service activity is to form a Breastfeeding Support Group (KP-ASI) through cadre training to create an exclusive breastfeeding aware family (KADARSIE). The results of the pre-test and post-test to determine the knowledge of cadres before and after training showed that there was an increase in knowledge of 26.7%, indicating that all cadres had good knowledge of exclusive breastfeeding materials after attending the training. The average score of cadres' attitudes towards exclusive breastfeeding was 82.7, indicating that cadres had a good attitude in supporting exclusive breastfeeding. The average score of breastfeeding technique skills is 86.1, and the average score of oxytocin massage skills is 84, indicating that almost all cadres have good skills as KP-ASI. The activity of optimizing the role of cadres in the formation of the ASI Support Group (KP-ASI) to realize the Exclusive Breastfeeding Awareness Family (KADARSIE) has been carried out. After the training, there was an increase in the knowledge of cadres about exclusive breastfeeding, and the attitude of cadres who support exclusive breastfeeding increased as well as increased skills of cadres in carrying out correct breastfeeding techniques and oxytocin massage.